Exploring the gap: attitudes, knowledge, and training needs in complementary and integrative medicine among healthcare professionals at German university hospitals - Hesmert, Daniela; Klocke, Carina; Stolz, Regina; Huber, Roman; Samstag, Yvonne; Hübner, Katrin; Simmet, Thomas; Syrovets, Tatiana; Joos, Stefanie; Valentini, Jan (Frontiers in Medicine, 2024)
Introduction: The use of Complementary and Integrative Medicine (CIM) is very popular among the general population in Germany. However, international studies show that health care professionals (HCPs) at hospitals often do not feel sufficiently informed about CIM. Moreover, they do not feel trained enough to counsel their patients appropriately. Particularly within university hospitals in the German-speaking area, research on this subject is scarce. Therefore, the aim of this explorative study was to evaluate attitudes, subjective knowledge, and needs regarding CIM among HCPs across all university hospitals in Baden-Württemberg, Germany. Methods: The full survey was conducted online using a web-based questionnaire. Recruitment took place via e-mail distribution lists of all four university hospitals. Results: Out of the n = 2,026 participants, nurses constituted the largest professional group (n = 1,196; 59 %), followed by physicians (n = 567; 28 %), physiotherapists (n = 54), psychologists (n = 48), midwives (n = 37), and other professions (n = 124). More than two-thirds (71 %, n = 1,437) of the participants were female and 14 % (n = 286) reported additional training in CIM. The overall attitude towards CIM was clearly positive (M ± SD: 7.43 ± 2.33) and CIM was incorporated by 41.7 % of the participants in patient care, both with notable differences between professional groups. Relaxation therapy (n = 1,951; 96 %), external applications (n = 1,911; 94 %), massage (n = 1,836; 91 %), and meditation/mindfulness (n = 1,812; 89 %) were rated as (rather) useful for patients. The average self-assessed knowledge level about CIM was moderate (M ± SD: 5.83 ± 2.03). Most participants rated CIM training and research important and as a task of university hospitals. Discussion: This survey of HCPs at university hospitals in Germany reveals a clearly positive disposition towards CIM, aligning with findings from other surveys and highlighting differences among professional groups. While most therapies deemed beneficial for patient care are supported by positive evidence, further research is required for others. Targeted education seems to be essential to meet the needs of both HCPs and patients and to ensure the provision of evidence-based information.